Water Jasmine (Echinodorus palaefolius): A Phytoremediation Agent for Environmental Health Improvement and Landscape Enhancement - Sari, Mellyaning Oktaviani Sonya Kirana (Universitas Karya Husada Semarang, 2026)
Background: Heavy metal and organic pollution in water bodies necessitate sustainable, cost-effective remediation. Echinodorus palaefolius is a potential aquatic macrophyte that offers a nature-based solution by combining pollutant removal with aesthetic value. Objective: This review evaluates the dual-purpose efficacy of E. palaefolius in removing contaminants through constructed wetlands (CWs) and its integration into sustainable urban landscapes. Methods: The study synthesizes data on E. palaefolius performance in subsurface flow (SSF-CW) and free water surface (FWS-CW) systems. It analyzes physiological mechanisms, including rhizofiltration and phytoextraction, as well as the influence of substrates such as zeolite and charcoal on removal rates. Results: Findings indicate that E. palaefolius achieves over 90% removal efficiency for heavy metals such as mercury (Hg), iron (Fe), copper (Cu), and lead (Pb). The plant's extensive root system facilitates high bioconcentration, particularly for iron in stems and roots, without compromising metabolic functions. Furthermore, its ornamental features, broad leaves, and white inflorescences enhance the visual and ecological integrity of urban water features. Conclusion: E. palaefolius is a highly effective, multifunctional agent for water quality management. Its implementation as a tertiary treatment in industrial and urban settings provides an eco-friendly strategy for environmental health and landscape beautification.